Gambling with lottery stocks? - Andreas Oehler; Julian Schneider (Journal of Asset Management, 2022)
In this article, we assess whether German private investors gamble in the stock market. Other studies that have analyzed private investors' preferences with regard to lottery-like characteristics have used retail or discount brokerage data. They have shown that stock trading has common entertainment features with traditional gambling. In particular, clients of discount brokers may invest for speculative purposes and thus have disproportional preferences for lottery-like characteristics. In consequence, assessing preferences by solely using a subset of investors—associated brokerage clients—may lead to substantially biased results. We assess this issue by using SHS -base data from Deutsche Bundesbank which captures the aggregate holdings of the German private sector. In line with the research, we find that German private investors overinvest in stocks with lottery-like features. Yet, when assessing the economic significance of the aggregate overinvestment, the effect is negligible. Further, we do not find consistent evidence of skewness that positively affects the aggregate holdings of the private sector. As studies have identified preferences for skewness as a driving force for retail investors' stock purchases, our results challenge the preconceived notion of which characteristics actually induce (disproportional) private sector investments.
Keywords: G11; G12; 330; Lottery stocks; Private sector holdings